DAMPAK PELAKSANAAN PERATURAN GUBERNUR NO. 25 TAHUN 2017 PASAL 7 TENTANG KETENTUAN LIMA HARI KERJA TERHADAP KEHARMONISAN RUMAH TANGGA (STUDI DI KANTOR CAMAT SEKOTONG KABUPATEN LOMBOK BARAT) - Ulfa, Rahmatun; Elpipit, Elpipit; Saputra, Wawan (Al-Muqaronah: Jurnal Perbandingan Madzhab dan Hukum, 2022)
The results of this research show that the perception of male and female employees at the Subdistrict Office regarding the five-day working day provision is that all of them say that they dominate the families of male and female employees at the Sekotong Subdistrict Office to support their families even though they have to work up to five working days, this It can be seen from the jobs of husband and wife whose income is different. Looking at the results of interviews conducted by researchers, the perceptions of male and female employees regarding the five-day working day provisions in the Sekotong Subdistrict Office environment are more focused because they have to follow regulations that must be obeyed and work also because of economic factors. The impact of marriages carried out while still working has positive and negative implications for household harmony. It has positive implications, namely the creation of a harmonious family and more enthusiasm in carrying out daily activities (earning a living) because marriage is carried out with careful planning, full of responsibility, honesty, and mutual understanding within the family, developing the principles of deliberation, openness to each other, respecting each other, plus the husband support his wife's career. Meanwhile, the negative implications are that the family is not in harmony, because they have to work from morning to evening, even longer than office hours because they have to complete unfinished office work. There is no time for family, lack of communication and lack of love for wife and children and seeing the weak economic condition of the family. Apart from that, if a husband and wife both work from morning to evening, problems will arise in the family, such as lack of attention, lack of communication between wife and children and lack of togetherness (staying overnight).